QUALITY AVALIATION OF THE CARE PROVIDED TO PATIENTS WITH VENOUS ULCER (Fiep Bulletin - online, 2013)
Rate is a necessary step when it established the goal of seeking the quality of health care. In our practice, we have noticed that the assistance to people with venous ulcers (UVS) is not contributing to effective treatment and prevention of new ulcers. Thus, we feel the need to evaluate the quality of care provided to patients with UVS seen at University Hospital Onofre Lopes (HUOL), in the city of Natal / RN. It is a descriptive study, where the population was composed of 40 individuals with UV, seen by arms, in the outpatient surgical clinic of this hospital. Data collection was conducted through structured interviews, non-participant observation during the exchange of healing and consultation with the medical records of patients. The Ethics Committee of Federal University of Rio Grande do Norte was in favor of the study (Protocol n.169/06). With this study, which evaluated the assistance given to the customer for UVS carriers was inadequate in various aspects concerning the involvement of interdiscilplinary team, conducting laboratory tests and specific in the last year, availability of products used in dressings made in the clinic and an indication of products used in dressings conducted outside the clinic, and appropriate for the indication of products used in dressings made in the clinic. A health service to deliver efficient must present structure and process organized. The structure of health services must be accessible, have qualified professionals in adequate number to the demand, with an operating physical infrastructure. The process should be systematized.
Keywords: Evaluation; Quality; assistance